P Penetapan Kadar Flavonoid Total dan Nilai Sun Protection Factor (SPF) Fraksi Ekstrak Etanol Daun Sirih Muda (Piper betle L.) - Deviani, Norma; Hakim, Ali Rakhman; Ikeh, Tri Sulapmi D.; Nastiti, Kunti (LPPM Universitas Sari Mulia, 2024)
Background: Betel leaf (Piper betle L.) is a plant that contains many important secondary metabolite compounds, one of which is the flavonoid group. empirically in the community, especially in South Kalimantan, who use these leaves as a mixture of cold powder using young betel leaves as protection against sunlight.Objective: To determine the total flavonoid content of the young betel leaf extract fraction (Piper betle L.) and the sun protection factor (SPF) value in the distilled water and ethyl acetate fractions.Methods: The experimental method with a posttest-only control group design involved qualitative analysis using thin layer chromatography (TLC) and quantitative data using UV-Vis spectrophotometry to determine total flavonoid levels and sun protection factor (SPF) values using the Mansur method.Results: The TLC analysis confirmed the presence of flavonoid compounds. Quantitative analysis using UV-Vis spectrophotometry showed total flavonoid content of 14.4 mg EQ/g (1.44%) in distilled water and 16.4 mg EQ/g (1.64%) in the ethyl acetate fraction. The highest SPF value was 17.29 at 600 ppm in the ethyl acetate fraction (ultra protection), while the lowest was in the distilled water fraction at 200 ppm (minimum category).Conclusion: The young betel leaf extract fractions showed that the distilled water fraction contained 14.4 mg EQ/g (1.44%) flavonoids, while the ethyl acetate fraction had 16.4 mg EQ/g (1.64%). The highest SPF value of 17.29 (ultra protection) was found in the ethyl acetate fraction at 600 ppm.